Pengaruh Literasi Keuangan, Pengetahuan Investasi, dan Motivasi Terhadap Keputusan Berinvestasi Mahasiswa di Pasar Modal Syariah - Okca Fiani Triana; Deny Yudiantoro (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2022)
This research is aims to examine the effect of financial literacy, knowledge of investment and motivation on students investment decisions in the sharia capital market. This research is carried out using quantitative approaches that obtain primary data from the spread of questionnaire. The data analysis carried out is the analysis of multiple linier regression. The population in this study were PTKIN student from East Java majoring in Sharia financial management, totaling 2.358 students. The sample used based on the slovin formula is 96 students. The result of this research show that financial literacy and knowledge of investment have an influence on students investmen decisions in the sharia capital market. Meanwhile, motivation do not have an effect on students investmen decisions in the sharia capital market Keyword : Financial literacy, knowledge of investment, motivation, sharia capital market